1990
DOI: 10.2307/3430944
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions in Epidemiologic Studies of 1,3-Butadiene-Exposed Workers

Abstract: To date, epidemiologic research on 1,3-butadiene has consisted of cohort mortality studies of workers in the styrene-butadiene rubber (SBR) and butadiene monomer industries. These studies have been extremely useful both in defining the focus on human health effects to the lymphopoietic cancers and in providing a perspective on which to evaluate the available animal models for human risk assessment. The next step for epidemiologic research will involve a lymphopoietic cancer case control approach to enable a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…No other details of the case-referent study were reported, although Acquavella (15) has indicated that there was no validation of the death certificate diagnoses, and the exposure classification did not make use of available industrial hygiene monitoring data, nor did it consider differences in exposure potential across the eight plants. Additional research is being done on this cohort to address these criticisms (15).…”
Section: Discussionmentioning
confidence: 99%
“…No other details of the case-referent study were reported, although Acquavella (15) has indicated that there was no validation of the death certificate diagnoses, and the exposure classification did not make use of available industrial hygiene monitoring data, nor did it consider differences in exposure potential across the eight plants. Additional research is being done on this cohort to address these criticisms (15).…”
Section: Discussionmentioning
confidence: 99%
“…Probably the most efficient approach to achieving this goal will be to create job-exposure matrices in alreadyestablished cohorts and then to undertake nested casecontrol studies (24). Also, additional toxicologic studies will be required to better delineate the mechanisms of carcinogenicity of 1,3-butadiene (2,16).…”
Section: Resultsmentioning
confidence: 99%
“…Criticism has been leveled against the apparent consistency of these epidemiologic findings on the ground that different subtypes of lymphatic and hematopoietic neoplasms were seen in the different studies (8,9,15,16). However, it is important to realize that the diagnostic categories in this area are imprecise and overlapping (17).…”
Section: Discussionmentioning
confidence: 99%
“…Because the epidemiology studies lacked quantitative exposure data, some have considered duration of employment within broad work job classifications to be an indication of human exposure (46,47). This relationship is probably not valid for the 1,3-butadiene or styrene-butadiene rubber production industries because there have been large variabilities in exposures associated with specific tasks, especially during the rapid growth of the synthetic rubber industry during World War II, and because process changes in the production of 1,3-butadiene and in the production ofstyrene-butadiene rubber probably affected workplace exposures over the past 50 years.…”
Section: Epidemiology Studiesmentioning
confidence: 99%